STUDY OF THE DESIGNS OF BOTTOM BLOWING DEVICES FOR OXIDATIVE BLOWING IN TEEMING LADLES (Modern Problems of Metallurgy, 2021)
It is discussed in the article the concept proposed for the production of ultra-low carbon steel, which involves the production of crude steel in basic oxygen furnace followed by oxidative blowing with an oxygen-argon mixture in a teeming ladle to decrease a carbon content in steel to less than 0.03%. High efficiency of the proposed technology is possible only under the intensive process of metal decarburization, which consists of the three stages: supply of reagents to the gas bubble, chemical interaction of reagents on the interfacial surface and removal of reaction products. At low carbon concentrations in the metal, the limiting link of the process is carbon mass transfer to the interfacial surface, which can be intensified by melt stirring. The objective of this article is to study the influence of design of the blowing devices, namely, the position and shape of the pores, on the efficiency of metal homogenization in the teeming ladle. Blowing devices with a circular hole, a slit and undirectional porosity were considered. To perform physical simulation by Buckingham's theorem, similarity numbers were chosen to describe the considered process. In particular, it is proposed to use dimensionless volume flow and a modified homochronicity number. Based on the physical simulation on the “water” model, it was found that the best results of homogenization of the chemical composition of the liquid metal in the teeming ladle show blowing devices with undirected porosity. They are ideal for oxidative purging in a crowded ladle with a mixture of argon and oxygen required for the production of ultra-low carbon steel with an oxygen content of less than 0.03%. The purpose of further research is to develop the design of the mixing chamber of the purge device, in which oxygen and argon are pre-mixed before injection into the liquid metal.
Keywords: steel; homogenization; ultra-low carbon steel; oxidative blowing